High-impedance near-zero-temperature-drift high-temperature piezoelectric crystal material and growth method and application thereof
By adopting ErxGd1-xCa4O(BO3)3 high-temperature piezoelectric crystal material and using lifting method growth and annealing treatment technology, the problem of large piezoelectric performance change rate in high-temperature environments has been solved, and the near-zero temperature drift high-temperature piezoelectric performance and high impedance stability in the range of 20~1000℃ is achieved, meeting the sensing application needs of 1000℃ with temperature resistance.
Patent Information
- Application Number
- CN202411737581.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing RECOB series high-temperature piezoelectric crystals show a large rate of change in the temperature range of 20~1000℃, which limits its development and application in high-temperature environments, and the impedance is reduced in thermal cycle experiments, making it difficult to meet the sensing application requirements of 1000℃ temperature resistance.
ErxGd1-xCa4O(BO3)3 (x=0.1~0.3) was used as high-temperature piezoelectric crystal material. Polycrystalline materials were prepared by stoichiometric ingredients of calcium source compounds, boron source compounds, erbium source compounds and gadolinium source compounds in stoichiometric ingredients, and single crystal growth was performed in the direction of (010) by lifting method, and finally annealed under an oxygen-containing atmosphere to obtain a near-zero temperature drift high-temperature piezoelectric crystal material.
It achieves near zero temperature drift high-temperature piezoelectric performance in the range of 20~1000℃, has high piezoelectric constant, resistivity and piezoelectric performance stability, can meet the research and development needs of piezoelectric sensors with temperature resistance of 1000℃, and maintains the stability of high-voltage electrical constant and impedance value in a high-temperature environment of 1000℃.
Smart Images

Figure CN119710894A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric crystal growth, and in particular to a high-impedance, near-zero temperature drift, high-temperature piezoelectric crystal material, a growth method and an application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Piezoelectric sensors have important applications in aerospace, automotive industry, nuclear power energy, and intelligent manufacturing due to their simple structure, good stability, wide operating temperature range, and strong anti-electromagnetic interference capabilities. Under actual working conditions, sensors often have to withstand high temperatures of 482°C or even above 650°C to monitor the health of the structure for a long time, which places high demands on the high temperature resistance and working stability of sensor materials. In response to the above application requirements, researchers have explored a variety of piezoelectric materials, including piezoelectric ceramics and piezoelectric crystals. The operating temperature of piezoelectric ceramics is limited by their Curie temperature. The Curie temperature of most piezoelectric ceramics is usually lower than 350°C, while piezoelectric ceramics with high Curie temperatures (such as calcium bismuth niobate, calcium bismuth titanate, etc.) have low resistivity at high temperatures, and the device operating temperature does not exceed 482°C, so applications at higher temperatures are still limited.
[0004] Compared with piezoelectric ceramics, piezoelectric crystal materials can avoid the influence of Curie temperature, and obtain low loss, high impedance and good temperature stability of piezoelectric performance. Lithium niobate (LiNbO3, LN) crystal has a Curie temperature of up to 1200℃, good piezoelectric and mechanical properties, and an effective piezoelectric constant d eff The operating temperature is ~70 pC / N, but due to oxygen loss and high temperature attenuation, the operating temperature generally does not exceed 650°C. 14 , LGS) series crystals have no phase change before the melting point (~1470℃), have a large piezoelectric constant and good temperature stability, and are the preferred materials for preparing high-temperature piezoelectric sensors. However, the presence of its disordered structure leads to a decrease in the high-temperature resistivity and an increase in the high-temperature loss of the crystals. The expensive price of Ga2O3 raw materials also limits its large-scale growth and application. Compared with the above-mentioned high-temperature piezoelectric materials, the rare earth calcium oxyborate (RECa4O(BO3)3, RECOB, RE: rare earth elements) series crystals have a high melting point (~1500℃) and no phase change before the melting point. They have lower losses, higher resistivity and better temperature stability of piezoelectric performance, providing an important material basis for the design and development of high-temperature piezoelectric sensors. In addition, this series of crystals is easy to grow by the Czochralski method, and it is easy to obtain large-size high-quality single crystals at a low cost.
[0005] At present, many studies have been conducted on RECOB series high-temperature piezoelectric crystals, and it has been found that this type of crystal has excellent high-temperature piezoelectric and dielectric properties. However, the piezoelectric properties of the currently developed RECOB series high-temperature piezoelectric crystals show a large change rate in the entire temperature range (20℃~1000℃), and their piezoelectric constant d 26 The maximum change rate even exceeds 30%, which limits the development and application of this type of piezoelectric crystal in high temperature environments. 26 The high temperature resistance of piezoelectric crystals with a low rate of change is relatively low. In 2014, Yu Fapeng and others from Shandong University developed a variety of new rare earth calcium oxyborate crystals, including YGdCOB, YSmCOB and GdLaCOB. 0.3 G 0.7 Piezoelectric constant d of COB crystal 26 It shows a low change rate of about -3% from room temperature to 900°C, but the inventors found that its impedance decreased significantly during the thermal cycling experiment, making it difficult to meet the sensor application requirements of 1000°C temperature resistance in actual complex environments.
[0006] Therefore, how to provide a piezoelectric crystal with near-zero temperature drift characteristics in the temperature range of 20~1000℃ and high impedance stability in a high temperature environment is an urgent problem to be solved. Summary of the invention
[0007] In view of this, the present invention provides a high-impedance, near-zero temperature drift, high-temperature piezoelectric crystal material, and a growth method and application thereof. The piezoelectric crystal material provided by the present invention can achieve near-zero temperature drift, high-temperature piezoelectric performance, has a higher piezoelectric constant, higher resistivity and higher piezoelectric performance stability, and can meet the research and development needs of piezoelectric sensors with a temperature resistance of 1000°C.
[0008] In the first aspect, the present invention provides a high impedance near zero temperature drift high temperature piezoelectric crystal material, the chemical formula of which is Er x G 1-x Ca4O(BO3)3, x=0.1~0.3.
[0009] Preferably, x=0.2.
[0010] In a second aspect, the present invention provides a method for growing the above-mentioned high-impedance near-zero temperature drift high-temperature piezoelectric crystal material, comprising the following steps: A calcium source compound, a boron source compound, an erbium source compound and a gadolinium source compound are mixed in a stoichiometric ratio to obtain a mixed material, wherein the boron source compound is in excess of 1-2 wt %; and then a polycrystalline material is prepared; The polycrystalline material is melted, and after adding the seed crystal, a single crystal is grown along the (010) direction by using the Czochralski method. After the growth is completed, the temperature is kept constant for a set time, and then cooled to room temperature to obtain the calcium borate erbium oxide gadolinium crystal; The calcium borate oxide erbium gadolinium crystal is annealed in an oxygen-containing atmosphere to obtain a near-zero temperature drift high-temperature piezoelectric crystal material.
[0011] Preferably, the calcium source compound is selected from calcium carbonate or calcium oxide; the boron source compound is selected from boric acid or boron oxide; the erbium source compound is selected from erbium oxide; and the gadolinium source compound is selected from gadolinium oxide.
[0012] Preferably, the steps for preparing the polycrystalline material are as follows: sintering the mixed material once at 900-950°C for 8-20 hours; mixing it for 10-20 hours after grinding, and then pressing it into blocks, and sintering it twice at 1100-1150°C for 20-30 hours to obtain the polycrystalline material.
[0013] Preferably, the step of melting the polycrystalline material is specifically as follows: heating the polycrystalline material to full melt under gas protection, then cooling it down to solidify it, repeating the steps of heating the polycrystalline material to full melt and cooling it down to solidify it 2 to 4 times, then heating the polycrystalline material to 20 to 40° C. above the melting point and keeping the temperature constant for 2 to 5 hours.
[0014] Furthermore, the gas is a mixed gas of oxygen and an inert gas, the volume fraction of oxygen is 1-5%, and the inert gas is selected from one or more of nitrogen or rare gases.
[0015] Preferably, the seed crystal is selected from GdCa4O(BO3)3, ErCa4O(BO3)3 or crystals of the same structure as GdCa4O(BO3)3 and ErCa4O(BO3)3.
[0016] Preferably, after the single crystal growth is completed, the temperature is maintained at a constant level for 40 to 120 minutes, and then the temperature is lowered to room temperature at a rate of 15 to 30° C. / h to obtain calcium borate erbium oxide gadolinium crystals.
[0017] Preferably, in the step of annealing the calcium borate erbium oxide gadolinium crystal in an oxygen-containing atmosphere, the oxygen-containing atmosphere is a mixture of oxygen and nitrogen, wherein the volume fraction of oxygen is 20-30%; the annealing temperature is 900-1100° C., and the annealing time is 48-72 hours.
[0018] In the third aspect, the present invention provides an application of the above-mentioned high-impedance near-zero temperature drift high-temperature piezoelectric crystal material or the high-impedance near-zero temperature drift high-temperature piezoelectric crystal material prepared by the above-mentioned preparation method, and the application is application in piezoelectric ultrasonic transducers, piezoelectric vibration sensors, piezoelectric acceleration sensors or piezoelectric pressure sensor devices.
[0019] Compared with the prior art, the present invention has achieved the following beneficial effects: (1) Er provided by the present invention x G 1-x The relative dielectric constant of Ca4O(BO3)3 (x=0.1~0.3) is =9~10, =11~14, =9~10, piezoelectric constant d 26 =8.5~10.0 pC / N, electromechanical coupling coefficient k 26 =20%~22%. The effective longitudinal piezoelectric constant d 33 Can reach 6.5~7.0pC / N; effective shear piezoelectric constant d 26 The resistivity can reach 8.5~10.0 pC / N; the resistivity can reach 10 at high temperature of 1000℃ 6 The piezoelectric constant has a change rate of less than 5% in the range of room temperature to 1000℃, and can be as low as less than 3%. It has near-zero temperature drift characteristics and good high temperature resistance. Even after thermal cycling for 70h at 1000℃, it still maintains high piezoelectric constant stability and impedance value stability.
[0020] (2) Er of the present invention x G 1-x Ca4O(BO3)3 (x=0.1~0.3) crystals can be grown by conventional Czochralski method to obtain large-sized high-quality single crystals. The growth process is simple and easy to process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 is Er grown in Example 1 of the present invention 0.2 G 0.8 COB high temperature piezoelectric crystals and the cut types used for testing; Figure 2 is Er grown in Example 1 of the present invention 0.2 G 0.8 COB high temperature piezoelectric crystal and Y of comparative example 4 0.3 G 0.7 COB crystal longitudinal piezoelectric constant d 33 The maximum value changes from room temperature to 650℃, with the inset showing Er 0.2 G 0.8Longitudinal piezoelectric constant d of COB high temperature piezoelectric crystal 33 The curve of the change with the rotation angle when rotating around the Z axis; Figure 3 is Er grown in Example 1 0.2 G 0.8 COB high temperature piezoelectric crystal and Y of comparative example 4 0.3 G 0.7 Comparison of high temperature resistivity of COB crystals; Figure 4 is Er grown in Example 1 0.2 G 0.8 COB and Comparative Example 4 0.3 G 0.7 The piezoelectric constant d of the COB high temperature piezoelectric crystal measured after thermal cycling for 70 hours at 1000℃ 26 ; Figure 5 is Er grown in Example 1 0.2 G 0.8 COB and Comparative Example 4 0.3 G 0.7 Impedance curves of the ZX-cut COB high-temperature piezoelectric crystal after thermal cycling for 0h and 70h at 1000℃; Figure 6 Is to use Er 0.2 G 0.8 Image of special-shaped piezoelectric components made from COB high-temperature piezoelectric crystals. DETAILED DESCRIPTION
[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0024] Explanation of terms Piezoelectric crystal: refers to a non-centrosymmetric crystal that deforms under the action of mechanical force, causing the charged particles to undergo relative displacement, resulting in positive and negative bound charges on the crystal surface. Such a crystal is called a piezoelectric crystal.
[0025] Piezoelectric constant: Longitudinal piezoelectric constant d ii (i=1,2,3), indicating that when the wafer is subjected to longitudinal stress X i After (i=1,2,3), polarization charges are generated on the upper and lower electrode surfaces of the chip, and the corresponding polarization intensity component is P i (i=1,2,3), and the polarization component P i (i=1,2,3), and stress X i(i=1,2,3) is proportional, and the proportionality coefficient is d ii (i=1,2,3), that is, P i =d ii X i .
[0026] Relative dielectric constant: Dielectric constant It indicates the change in electric displacement caused by a unit change in electric field intensity in the X direction under the condition of zero strain. The dielectric constant The dielectric constant of vacuum The ratio of . Relative dielectric constant and Same reason.
[0027] Temperature drift: refers to the drift of the crystal piezoelectric coefficient with temperature (with room temperature data as a reference). This parameter describes the stability of the performance of piezoelectric components or crystal elements within the temperature change range. The near-zero temperature drift proposed in the present invention means that within the entire test temperature range, the rate of change of the measured parameter relative to the value at room temperature is close to zero.
[0028] Electromechanical coupling coefficient: During the vibration process, the piezoelectric chip converts mechanical energy into electrical energy, or converts electrical energy into mechanical energy. The degree of mutual energy conversion is expressed by the electromechanical coupling coefficient.
[0029] Thickness shear electromechanical coupling coefficient k 26 : Refers to the parameters of the electromechanical coupling effect when a rectangular piece of piezoelectric crystal is polarized along its length and the direction of the excitation electric field is perpendicular to the polarization direction and undergoes thickness shear vibration.
[0030] Er x G 1-x Ca4O(BO3)3(Er x G 1-x COB) Crystal piezoelectric physical axis: For the crystal of m point group, the physical coordinate axis Z is parallel to the crystallographic coordinate axis c, the physical coordinate axis Y is parallel to the crystallographic coordinate axis b, and the X axis is determined by the right-hand screw rule. It should be further pointed out that for Er x G 1-x For Ca4O(BO3)3 crystal, the +Z direction is related to the piezoelectric constant d 33 The positive direction is consistent with the piezoelectric constant d 11 The positive direction is consistent with that of the quasi-static d 33 Tester OK.
[0031] The present invention provides a high-impedance near-zero temperature drift high-temperature piezoelectric crystal material, the chemical formula of which is Erx G 1-x Ca4O(BO3)3, x=0.1~0.3.
[0032] The Er provided by the present invention x G 1-x Ca4O(BO3)3 piezoelectric crystal material (Er x G 1-x The melting point of COB is about 1450°C, there is no phase change from room temperature to the melting point, it has a non-centrosymmetric structure, and belongs to the monoclinic m point group. In this crystal, rare earth gadolinium and rare earth erbium occupy each other's lattice sites. The angle between the crystal axis a axis and the piezoelectric physical axis X of the crystal material is close to (a, X) = 11.2°, and the angle between the crystal axis c axis and the piezoelectric physical axis Z is (c, Z) = 0°; the crystal axis b is parallel to the piezoelectric physical axis Y, and the piezoelectric physical axes X, Y and Z follow the right-hand screw rule.
[0033] The present invention finds that the value of x, i.e. the molar ratio of Er element to Gd element, has a great influence on the temperature stability of the obtained piezoelectric crystal material. If x is too large or too small, the piezoelectric constant change rate is too high and the material cannot be used stably in a high temperature environment of 1000°C.
[0034] In the present invention, x=0.2, that is, the chemical formula of the high impedance near zero temperature drift high temperature piezoelectric crystal material is Er 0.2 G 0.8 Ca4O(BO3)3. The present invention finds that when x is close to 0.2, the piezoelectric crystal material has the best piezoelectric constant stability.
[0035] The present invention also provides a method for growing the above-mentioned high-impedance near-zero temperature drift high-temperature piezoelectric crystal material, comprising the following steps: A calcium source compound, a boron source compound, an erbium source compound and a gadolinium source compound are mixed in a stoichiometric ratio to obtain a mixed material, wherein the boron source compound is in excess of 1-2 wt %; and then a polycrystalline material is prepared; The polycrystalline material is melted, and after adding the seed crystal, a single crystal is grown along the (010) direction by using the Czochralski method. After the growth is completed, the temperature is kept constant for a set time, and then cooled to room temperature to obtain calcium borate erbium oxide gadolinium crystal; The calcium borate oxide erbium gadolinium crystal is annealed in an oxygen-containing atmosphere to obtain a near-zero temperature drift high-temperature piezoelectric crystal material.
[0036] The high impedance near zero temperature drift high temperature piezoelectric crystal material Er of the present invention x G 1-x Ca4O(BO3)3 is a non-centrosymmetric m-point group crystal configuration with good mechanical properties, is not easy to deliquesce, melts uniformly, and can be grown into large-sized high-quality single crystals in a relatively short time using the Czochralski method.
[0037] In the present invention, the calcium source compound is selected from calcium carbonate; the boron source compound is selected from boric acid or boron oxide; the erbium source compound is selected from erbium oxide; and the gadolinium source compound is selected from gadolinium oxide. The present invention does not impose any special restrictions on the sources of the above raw materials, and the purity of all raw material compounds must reach 99.99% or more.
[0038] After the batching is completed, the present invention further includes a step of mixing the materials. The present invention does not impose any special restrictions on the mixing step, as long as a uniformly mixed material can be obtained.
[0039] The present invention adopts the method of excess boron source compound to compensate for the component deviation caused by the volatilization of boron during the crystal growth process, and "excess boron source compound 1-2wt%" refers to the total mass of the mixed material.
[0040] In the present invention, the steps of preparing the polycrystalline material are as follows: the mixed material is sintered once at 900-950°C for 8-20 hours; after grinding, it is mixed for 10-20 hours, and then pressed into blocks, and sintered twice at 1100-1150°C for 20-30 hours to obtain the polycrystalline material. The first sintering of the present invention is to pre-decompose the carbonate material in the raw material to reduce the generation of bubbles in the subsequent polycrystalline material melt. The particle size of the ground product after the first sintering is preferably 10-20 μm, so as to ensure the quality of crystal growth.
[0041] In the present invention, the step of melting the polycrystalline material is specifically as follows: heating the polycrystalline material to full melting under gas protection, then cooling it to condense it, repeating the steps of heating the polycrystalline material to full melting and cooling it to condense it 2 to 4 times, and then heating the polycrystalline material to 20 to 40°C above the melting point, and keeping the temperature constant for 2 to 5 hours. Repeated heating melting-cooling condensation steps completely exhaust the bubbles generated in the melt to reduce crystal growth defects (bubbles and inclusions, etc.) and improve the quality of crystal growth. The present invention does not impose any special restrictions on the equipment used in the melting process of the polycrystalline material, and the equipment commonly used in the art can be used. The gas in the melting process of the polycrystalline material is preferably a mixed gas of oxygen and an inert gas, the volume fraction of oxygen is 1 to 5%, and the inert gas is selected from one or more of nitrogen or a rare gas. The oxygen content in the growth process of the YGdCOB crystal will affect the change of its microstructural disorder, thereby affecting the electroelastic properties of the crystal material.
[0042] In the present invention, the seed crystal is selected from GdCa4O(BO3)3, ErCa4O(BO3)3 or crystals of the same structure as GdCa4O(BO3)3 and ErCa4O(BO3)3, preferably GdCa4O(BO3)3. x G 1-xCa4O(BO3)3 crystals grow faster along the crystal axis (010), i.e., the b direction, and have higher crystal quality, so it is preferred to grow crystals along the (010) direction. The b-direction seed crystal can be obtained by the following method: 3、 GdCa4O(BO3)3 or other isomorphous crystals can be processed along their crystal axis b to obtain b-direction seed crystals.
[0043] The single crystal growth process of the present invention includes four stages: necking, shoulder release, equal diameter growth and lifting. During the necking process, the pulling speed is 1-3 mm / h and the rotation speed is 4-8 rpm; when the seed crystal diameter is reduced to 1-1.5 mm, the temperature is slowly reduced at a rate of 0.5-5°C / h to release the shoulder; during the shoulder release process, the pulling speed is reduced to 0.5-1 mm / h and the rotation speed is 6-8 rpm; when the diameter of the crystal shoulder reaches a predetermined size of 20-40 mm, the temperature is increased or decreased at a rate of 0-2°C / h to perform equal diameter growth; during equal diameter growth, the pulling speed is 0.3-0.6 mm / h and the rotation speed is 6-8 rpm; when the crystal is pulled to a height of 40-60 mm, the crystal is ready to be lifted. The specific operation of the preferred stripping process of the present invention is as follows: slowly increase the temperature at a rate of 20-50°C / h, while increasing the pulling speed to 5-10mm / h and the rotation speed to 8-12rpm. When it is observed that the bottom of the crystal has a tendency to shrink inward, manual pulling is performed to pull the crystal out of the melt.
[0044] In the present invention, after the single crystal growth is completed, the temperature is kept constant for 40 to 120 minutes, and then the temperature is cooled to room temperature at a rate of 15 to 30°C / h to obtain calcium borate erbium oxide gadolinium crystal. A suitable cooling rate is conducive to obtaining a crystal with higher piezoelectric performance stability.
[0045] In the present invention, in the step of annealing the calcium borate erbium oxide gadolinium crystal in an oxygen-containing atmosphere, the oxygen-containing atmosphere is a mixture of oxygen and nitrogen, wherein the volume fraction of oxygen is 20-30%; the annealing temperature is 900-1100° C., preferably 1000° C.; the annealing time is 48-72 hours, preferably 55-65 hours, so that the thermal stress generated during the crystal growth process is fully released and the microstructure disorder degree reaches a large level.
[0046] The present invention provides an application of the above-mentioned high-impedance near-zero temperature drift high-temperature piezoelectric crystal material or the high-impedance near-zero temperature drift high-temperature piezoelectric crystal material prepared by the above-mentioned preparation method, and the application is: application in piezoelectric ultrasonic transducers, piezoelectric vibration sensors, piezoelectric acceleration sensors or piezoelectric pressure sensor devices, which can work stably in the range of 20~1000℃, and are particularly suitable for high temperature environments of 850~1000℃.
[0047] The technical solution of the present invention is further described below in conjunction with specific embodiments. The purity of the raw materials in the following embodiments is greater than 99.99%.
[0048] Example 1 This embodiment provides a calcium borate erbium oxide gadolinium high temperature piezoelectric crystal material Er 0.2 G 0.8 COB, its chemical formula is Er 0.2 G 0.8 Ca4O(BO3)3. The growth method includes the preparation of polycrystalline material and the growth of crystal by Czochralski method, and the steps are as follows: (1) Using CaCO3, H3BO3, Er2O3, and Gd2O3 as raw materials, according to the chemical formula Er 0.2 G 0.8 The mixture is prepared in a stoichiometric ratio of Ca4O(BO3)3, wherein the amount of boric acid in excess is 1.5% of the total mass of the mixture, and then mixed in a mixer for 32 hours to make it fully mixed.
[0049] (2) The fully mixed raw materials were placed in a ceramic crucible for the first sintering at a temperature of 930° C. for 10 hours to decompose and remove CO2 and H2O; after cooling to room temperature, the raw materials for the first sintering were placed in a grinder for 1 hour and then mixed again for 16 hours, pressed into a material block with a diameter of 50 mm, and placed in a ceramic crucible for the second sintering to cause a solid phase reaction at a temperature of 1150° C. for 24 hours to obtain calcium borate erbium oxide gadolinium polycrystalline material.
[0050] (3) placing the calcium borate erbium oxide gadolinium polycrystalline material obtained in step (2) into a platinum crucible in a single crystal furnace, evacuating the furnace and filling it with nitrogen and oxygen as protective gases, wherein the volume fraction of oxygen is controlled at 2%, heating the polycrystalline raw material to melt by medium frequency induction heating, cooling the polycrystalline material to condense after it is fully melted, and then heating it again to melt it completely, repeating this process twice, removing bubbles generated in the melt, and then superheating the melt by 20° C. and keeping the temperature constant for 10 hours to obtain a uniformly melted calcium borate erbium oxide gadolinium polycrystalline melt; (4) Slowly immerse the seed crystal taken from the (010) direction of the GdCa4O(BO3)3 crystal into the polycrystalline melt of step (3) until the top of the seed crystal is perpendicular to and just in contact with the melt, and start growing the single crystal along the (010) direction; (5) The crystal growth process includes four stages: necking, shoulder release, equal diameter growth and lifting. In the necking process, the pulling speed is 1.5 mm / h and the rotation speed is 5 rpm. When the seed crystal diameter is reduced to 1 mm, the temperature is slowly reduced at a rate of 0.5 °C / h to release the shoulder. In the shoulder release process, the pulling speed is reduced to 0.5 mm / h. When the diameter of the crystal shoulder reaches the predetermined size of 30 mm, the temperature is increased or decreased at a rate of 1 °C / h to perform equal diameter growth. The pulling speed during equal diameter growth is 0.5 mm / h. When the crystal is lifted to a height of 50 mm, the crystal is ready to be lifted. The specific operation of the lifting process is as follows: the temperature is slowly increased at a rate of 20 °C / h, and the pulling speed is increased to 5 mm / h and the rotation speed is 10 rpm. When it is observed that the bottom of the crystal has a tendency to shrink inward, it is manually pulled to separate the crystal from the melt.
[0051] (6) After the crystal is extracted, the crystal is kept at a constant temperature for 1 hour in a temperature field and then cooled to room temperature at a rate of 20°C / h to obtain calcium borate erbium oxide gadolinium crystal.
[0052] (7) After the crystal is taken out, it is placed in a tubular furnace for annealing. The annealing atmosphere is 80% N2+20% O2, the annealing temperature is 1000°C, and the annealing time is 60h, so that the thermal stress generated during the crystal growth process can be fully released.
[0053] Example 2 This embodiment provides a calcium borate erbium oxide gadolinium high temperature piezoelectric crystal material Er 0.2 G 0.8 COB, its chemical formula is Er 0.2 G 0.8 Ca4O(BO3)3. The growth method includes the preparation of polycrystalline material and the growth of crystal by Czochralski method, and the steps are as follows: (1) Using CaCO3, H3BO3, Er2O3, and Gd2O3 as raw materials, according to the chemical formula Er 0.2 G 0.8 The mixture is prepared in a stoichiometric ratio of Ca4O(BO3)3, wherein the amount of boric acid in excess is 1% of the total mass of the mixture, and then mixed in a mixer for 32 hours to make it fully mixed.
[0054] (2) The fully mixed raw materials are placed in a ceramic crucible and sintered for the first time at a temperature of 930° C. for 10 hours to decompose and remove CO2 and H2O; after cooling to room temperature, the raw materials sintered for the first time are ground in a grinder for 1 hour, mixed again for 16 hours, pressed into a material block with a diameter of 50 mm, and placed in a ceramic crucible for a second sintering to cause a solid phase reaction at a temperature of 1150° C. for 24 hours to obtain a calcium borate erbium oxide gadolinium polycrystalline raw material.
[0055] (3) placing the calcium borate erbium oxide gadolinium polycrystalline material obtained in step (2) into a platinum crucible in a single crystal furnace, evacuating the furnace and filling it with nitrogen and oxygen as protective gases, wherein the volume fraction of oxygen is controlled to be 2%, heating the polycrystalline raw material to melt by medium frequency induction heating, cooling the polycrystalline material to condense after it is completely melted, and then heating it again to melt it completely, repeating this process three times, removing bubbles generated in the melt, and then superheating the melt by 30° C. and keeping the temperature constant for 3 hours to obtain a uniformly melted calcium borate erbium oxide gadolinium melt; (4) Slowly immersing a (010) oriented seed crystal taken from a GdCa4O(BO3)3 crystal into the polycrystalline melt of step (3) until the top of the seed crystal is perpendicular to and just in contact with the melt, and starting to grow a single crystal along the (010) direction; (5) The crystal growth process includes four stages: necking, shoulder release, equal diameter growth and lifting. In the necking process, the pulling speed is 1.5 mm / h and the rotation speed is 5 rpm. When the seed crystal diameter is reduced to 1 mm, the temperature is slowly reduced at a rate of 0.5 °C / h to release the shoulder. In the shoulder release process, the pulling speed is reduced to 0.5 mm / h. When the diameter of the crystal shoulder reaches the predetermined size of 30 mm, the temperature is increased or decreased at a rate of 1 °C / h to perform equal diameter growth. The pulling speed during equal diameter growth is 0.5 mm / h. When the crystal is lifted to a height of 50 mm, the crystal is ready to be lifted. The specific operation of the lifting process is as follows: the temperature is slowly increased at a rate of 20 °C / h, and the pulling speed is increased to 5 mm / h and the rotation speed is 10 rpm. When it is observed that the bottom of the crystal has a tendency to shrink inward, it is manually pulled to separate the crystal from the melt.
[0056] (6) After the crystal is extracted, the crystal is kept at a constant temperature for 1 hour in a temperature field and then cooled to room temperature at a rate of 20°C / h to obtain calcium borate erbium oxide gadolinium crystal.
[0057] (7) After the crystal is taken out, it is placed in a tubular furnace for annealing. The annealing atmosphere is 80% N2+20% O2, the annealing temperature is 1000°C, and the annealing time is 48 hours, so that the thermal stress generated during the crystal growth process can be fully released.
[0058] Comparative Example 1 The difference between this comparative example and Example 2 is that the high-temperature piezoelectric crystal material of this comparative example is erbium oxide calcium borate (ErCOB), whose chemical formula is ErCa4O(BO3)3, that is, Gd2O3 raw material is not added in the synthesis process.
[0059] Comparative Example 2 The difference between this comparative example and Example 2 is that the high-temperature piezoelectric crystal material of this comparative example is gadolinium calcium oxide borate (GdCOB), and its chemical formula is GdCa4O(BO3)3, that is, Er2O3 raw material is not added during the synthesis process.
[0060] Comparative Example 3 The difference between this comparative example and Example 2 is that the chemical formula of the calcium borate erbium oxide gadolinium high temperature piezoelectric crystal material in this comparative example is Er 0.5 G 0.5 Ca4O(BO3)3.
[0061] Comparative Example 4 The chemical formula of the calcium borate yttrium gadolinium high temperature piezoelectric crystal material of this comparative example is Y 0.3 G 0.7 Ca4O(BO3)3.
[0062] Test example The piezoelectric crystals grown in the embodiment and the comparative example were made into piezoelectric vibrators of different sizes, and the resistivity of the upper limit of the test temperature of the corresponding piezoelectric crystal was measured using a digital multimeter. The relative dielectric constant, electromechanical coupling coefficient and piezoelectric constant of each sample were measured using a balanced bridge method, an impedance method and a quasi-static method. The results are shown in Table 1.
[0063] Table 1 Test performance data of high temperature piezoelectric crystal materials
[0064] Note: The resistivity in Table 1 refers to the resistivity of the piezoelectric crystal material at 1000°C, and the piezoelectric constant change rate refers to the piezoelectric constant d of the piezoelectric crystal material within 25°C to 1000°C. 26 Rate of change.
[0065] It can be seen from the contents of Table 1 that the Er of the embodiment of the present invention 0.2 G 0.8 COB has good temperature stability of piezoelectric constant. The piezoelectric constant d in the range of 25~1000℃ is 26 The change rate is less than 5%, and it can withstand a high temperature environment of 1000℃, and the resistivity at 1000℃ can still reach 10 6 Ω·cm or above, it has higher impedance and better temperature stability and high temperature resistance of piezoelectric constant than the comparative piezoelectric crystal materials, can work stably in the range of 20~1000℃, and is especially suitable for high temperature environment of 850~1000℃.
[0066] Figure 1 is Er grown in Example 1 of the present invention 0.2 G 0.8 COB high temperature piezoelectric crystal and the cut type used for testing. Figure 2 is Er grown in Example 1 of the present invention 0.2 G 0.8 COB and Comparative Example 4 0.3 G 0.7Longitudinal piezoelectric constant d of COB high temperature piezoelectric crystal 33 The maximum value from room temperature to 650℃ change rate (when the longitudinal piezoelectric constant d 33 The maximum value is obtained when rotating 52° around the Z axis). It can be seen that Er 0.2 G 0.8 COB vs Y 0.3 G 0.7 COB has better stability. Figure 3 is Er grown in Example 1 0.2 G 0.8 COB and Comparative Example 4 0.3 G 0.7 The high temperature resistivity comparison of COB high temperature piezoelectric crystals shows that at high temperatures of 500~1000℃, Er 0.2 G 0.8 The resistivity of COB is always higher than that of Y 0.3 G 0.7 Resistivity of COB. Figure 4 is Er grown in Example 1 0.2 G 0.8 COB and Comparative Example 4 0.3 G 0.7 Piezoelectric constant d of COB high temperature piezoelectric crystal after thermal cycling at 1000℃ for 70 hours 26 Change graph, Figure 5 is Er grown in Example 1 0.2 G 0.8 COB and Comparative Example 4 0.3 G 0.7 The impedance curves of COB high temperature piezoelectric crystals after thermal cycling for 0h and 70h show that the Er grown in Example 1 0.2 G 0.8 COB high temperature piezoelectric crystal has excellent cycle performance, the piezoelectric constant value and impedance value change very little, and Y 0.3 G 0.7 The piezoelectric performance and impedance value of COB high-temperature piezoelectric crystal decreased significantly after 70 hours of cycling.
[0067] Application Examples The Er of Example 1 0.2 G 0.8 COB is used to prepare special-shaped piezoelectric components, and its macroscopic picture is as follows Figure 6 shown.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high impedance near zero temperature drift high temperature piezoelectric crystal material, characterized in that: The chemical formula of the near-zero temperature drift high temperature piezoelectric crystal material is Er x G 1-x Ca4O(BO3)3, x=0.1~0.
3.
2. The near-zero temperature drift high temperature piezoelectric crystal material according to claim 1, characterized in that: x=0.2。 3. The method for growing a high-impedance near-zero temperature drift high-temperature piezoelectric crystal material according to any one of claims 1 to 2, characterized in that: The steps include: A calcium source compound, a boron source compound, an erbium source compound and a gadolinium source compound are mixed in a stoichiometric ratio to obtain a mixed material, wherein the boron source compound is in excess of 1 to 2 wt%; and then a polycrystalline material is prepared; The polycrystalline material is melted, and after adding the seed crystal, a single crystal is grown along the (010) direction by using the Czochralski method. After the growth is completed, the temperature is kept constant for a set time, and then cooled to room temperature to obtain the calcium borate erbium oxide gadolinium crystal; The calcium borate oxide erbium gadolinium crystal is annealed in an oxygen-containing atmosphere to obtain a near-zero temperature drift high-temperature piezoelectric crystal material.
4. The growth method according to claim 3, characterized in that The calcium source compound is selected from calcium carbonate or calcium oxide; the boron source compound is selected from boric acid or boron oxide; the erbium source compound is selected from erbium oxide; and the gadolinium source compound is selected from gadolinium oxide.
5. The growth method according to claim 3, characterized in that The steps of preparing the polycrystalline material are as follows: sintering the mixed material once at 900-950°C for 8-20 hours; mixing it for 10-20 hours after grinding, and then pressing it into blocks, and sintering it twice at 1100-1150°C for 20-30 hours to obtain the polycrystalline material.
6. The growth method according to claim 3, characterized in that The step of melting the polycrystalline material is specifically as follows: heating the polycrystalline material to full melting under gas protection, then cooling it down to solidify it, repeating the steps of heating the polycrystalline material to full melting and cooling it down to solidify it 2 to 4 times, then heating the polycrystalline material to 20 to 40° C. above the melting point and keeping the temperature constant for 2 to 5 hours.
7. The growth method according to claim 6, characterized in that The gas is a mixed gas of oxygen and inert gas, the volume fraction of oxygen is 1-5%, and the inert gas is selected from one or more of nitrogen or rare gas.
8. The growth method according to claim 3, characterized in that The seed crystal is selected from GdCa4O(BO3)3, ErCa4O(BO3)3 or crystals with the same structure as GdCa4O(BO3)3 and ErCa4O(BO3)3.
9. The growth method according to claim 3, characterized in that: After the single crystal growth is completed, the temperature is kept constant for 40 to 120 minutes, and then the temperature is lowered to room temperature at a rate of 15 to 30° C. / h to obtain a calcium borate erbium oxide gadolinium crystal; in the step of annealing the calcium borate erbium oxide gadolinium crystal in an oxygen-containing atmosphere, the oxygen-containing atmosphere is a mixed gas of oxygen and nitrogen, wherein the volume fraction of oxygen is 20 to 30%; the annealing temperature is 900 to 1100° C., and the annealing time is 48 to 72 hours.
10. Use of the high impedance near zero temperature drift high temperature piezoelectric crystal material according to any one of claims 1 to 2 or the high impedance near zero temperature drift high temperature piezoelectric crystal material prepared by the preparation method according to any one of claims 3 to 9, characterized in that: Application in piezoelectric ultrasonic transducers, piezoelectric vibration sensors, piezoelectric acceleration sensors or piezoelectric pressure sensors.
Citation Information
Patent Citations
High-performance photoelectric functional calcium borate thulium oxide crystal and growth and application thereof
CN103422172A
High-temperature YxGd(1-x)Ca4O(BO3)3 piezoelectric crystal material as well as growth method and application thereof
CN104862774A
Blended ytterbium boric acid Gd yttrium oxygen calcium self-frequency doubling laser crystal
CN1609287A